Re-Interpretation of Mañjuśrī in Central and East Java - Lesley S Pullen (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
This article will begin with a brief look at the origins of Mañjuśrī from south Nepal, his popularity in China and the many depictions of him in eastern India and Java. More importantly, it will re-interpret a selected group of the Boddhisattva Mañjuśri in the human form with one head and two arms. The statues produced in both bronze, silver and stone, all with similar attributes identifying him as Mañjuśrī. The theoretical framework follows the various representation of Mañjuśrī statues from eastern India to a Kumārabhūta form only in Central Java and a single form of Arapacana in East Java. Within this framework, it will evaluate the stylistic features, attributes and the sartorial style of statues from both regions of Java, with details not previously discussed by past scholars, particularly looking at the textile patterns found on several of the statues.When the Mañjuśrī statues appeared in Central Java, various forms of the youthful Kumārabhūta or royal prince emerged, where he appeared to be particularly popular. Despite past knowledge of these statues, this paper allows for a new research direction and highlights the change in Mañjuśrī styles from Central to East Java. Similarly, various forms of Mañjuśrī Arapacana from eastern India transpire in East Java with this one unique statue of Arapacana from Caṇḍi Jago.